2009
DOI: 10.1108/14720700910984945
|View full text |Cite
|
Sign up to set email alerts
|

Embedding corporate responsibility and sustainability – everybody's business

Abstract: Purpose -This paper aims to deal with the significance of leadership as driver of corporate responsibility and complementary, dynamic organizational change. It seeks to focus on the continuous attention required by competitiveness, and the cultural complexity of renewing business processes in a global environment.Design/methodology/approach -The paper opens by adopting the insecurity context that is clearly reflected in a range of contemporary management and non-management discourses. Among the negative attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…We found that practitioners believed that performance in their job, and sustainability were separate ideas with separate responsibilities-which inhibits the transition to sustainability embeddedness [20,43,62].…”
Section: Not My Jobmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that practitioners believed that performance in their job, and sustainability were separate ideas with separate responsibilities-which inhibits the transition to sustainability embeddedness [20,43,62].…”
Section: Not My Jobmentioning
confidence: 99%
“…There are limited studies that have departed from the proactive orientation towards the adoption of a sustainability-embedded orientation [15,20,23,26,40]. Studies have also tended to focus on the operational changes required by organizations-such as strategies for reducing waste-often neglecting to examine organizations holistically in terms of both the operational and transformational changes required to shift to embeddedness [17,20,26,28,43,62].…”
Section: Research Purposementioning
confidence: 99%
See 1 more Smart Citation
“…The model represents a holistic approach to corporate governance and CSR that integrates company, shareholder, and wider stakeholder concerns. It recognises the paradox that society is demanding more of business while simultaneously trusting it less (Rake and Grayson 2009). The implication is that responsible CSR is no longer about individual projects or programmes, but rather how the totality of business activity impacts on organisation stakeholders such as customers, suppliers, employees, communities, government, and the environment (Rake and Grayson 2009).…”
Section: A Stakeholder Systems Model Of Csr: Overviewmentioning
confidence: 99%
“…Sustainability in most businesses is acknowledged as something important not only for competitive advantages, but something even indispensable for future survival of businesses. Yet their efforts and impact have not been creating the necessary improvements on a larger, global scale and most fail to provide for social and environmental needs (Metcalf & Benn, 2012;Rake & Grayson, 2009). This causes a significant disconnection between, on the one hand, what a company says that it should and wants to do, and on the other hand, its actual actions and their subsequent impacts (Dyllick & Muff, 2016).…”
Section: Targeting Businessesmentioning
confidence: 99%